2017
DOI: 10.2172/1411668
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Variable Renewable Energy on Bulk Power System Assets, Pricing, and Costs

Abstract: and Patrick Brown (MIT). Of course, any omissions or errors that remain are solely the responsibility of the authors. penetrations increase, but sometimes come at a cost to the consumer that is not always accounted for in generation portfolio decision-making. (see Chapters 2 and 5) All generation types are unique in some respect-bringing benefits and challenges to the power system-and wholesale markets, industry investments, and operational procedures have evolved over time to manage the characteristics of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 99 publications
(186 reference statements)
2
83
0
Order By: Relevance
“…For example, the economic value of offshore wind production along the East Coast of the United States varies with time and space, driven by electricity pricing and production fluctuations (Mills et al 2018). The value of offshore wind to a broader energy portfolio (including both renewable and non-renewable sources) is driven by both the seasonal and daily variability in power production from wind and the other sources, as well as seasonal and daily variations in grid demand for power (Sinden 2007, Fripp and Wiser 2008, Wiser et al 2017. Alignment between production and demand over seasonal and daily time scales is thus critical for reliability and functionality of the grid system (Shaner et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the economic value of offshore wind production along the East Coast of the United States varies with time and space, driven by electricity pricing and production fluctuations (Mills et al 2018). The value of offshore wind to a broader energy portfolio (including both renewable and non-renewable sources) is driven by both the seasonal and daily variability in power production from wind and the other sources, as well as seasonal and daily variations in grid demand for power (Sinden 2007, Fripp and Wiser 2008, Wiser et al 2017. Alignment between production and demand over seasonal and daily time scales is thus critical for reliability and functionality of the grid system (Shaner et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…National Laboratory prepared a study [2] that focused on the degree to which growth in VRE has impacted wholesale power prices and bulk power system assets to date and how this may change in the future. Here we present our synthesis of available literature, data and analysis on the degree to which growth in VRE has influenced or might in the future impact wholesale markets and generating assets in the U.S.…”
Section: As Input Into the Doe Staff Report Lawrence Berkeley Nationmentioning
confidence: 99%
“…Integral to the analysis is a framework for modeling renewables using a US-focused, long-term capacity planning model with detailed operations. The literature has demonstrated the importance of using models that capture the declining economic value of variable renewable energy at higher penetration levels (Hirth 2013, Blanford 2015, Gowrisankaran et al 2016, Bistline 2017, Wiser et al 2017. Figure 2 shows the economic intuition for how the equilibrium variable renewable share ('Share 1') jointly depends on the slopes of the marginal value curve ('Value') and marginal cost curve ('Cost 1'), which assumes that costs decline in deployment (Nordhaus 2014).…”
Section: Analytical Approachmentioning
confidence: 99%
“…wind and solar as penetration increases across a variety of conditions. Other studies have discussed the drivers and impacts of decreasing returns in observed and modeled systems(Hirth 2013, Blanford 2015, Gowrisankaran et al 2016, Bistline 2017, Wiser et al 2017, but this analysis underscores how dynamics like seasonal resource variability contribute to steep value declines with higher wind and solar shares, even with optimistic assumptions about the costs of backup resources with low utilization rates(Shaner et al 2018).…”
mentioning
confidence: 99%